A new species of Abyssocladia (Porifera, Demospongiae, Poecilosclerida, Cladorhizidae) and other carnivorous sponges from the far eastern Solomon Islands - Vacelet, Jean; Kelly, Michelle (Zootaxa, 2014)
Two species, one each of Abyssocladia Lévi, 1964, and Asbestopluma Topsent, 1901, are recorded from the far eastern Solomon Islands for the first time. Abyssocladia lakwollii sp. nov. is characterized by the pedunculate disc-shape of the body, the unusually large size of the isochelae I microscleres, and by the shape of the cleistochelae with crossed central teeth. Asbestopluma (A.) desmophora Kelly & Vacelet, 2011, first described from a seamount on Macquarie Ridge (Australia EEZ) and eastern waters to the north and south of New Zealand, is also recorded from the far eastern Solomon Islands. The specimens differ only slightly from their southern counterparts in dimensions of some spicules, and in the ornamentation detail of the basal teeth of the large and small anisochelae.